2019
DOI: 10.1200/jco.2019.37.7_suppl.33
|View full text |Cite
|
Sign up to set email alerts
|

Multi-institutional analysis of synchronous prostate and rectosigmoid cancers.

Abstract: 33 Background: Synchronous prostate cancer (PC) and rectosigmoid (RS) cancer (RSC) is a challenging clinical situation. Methods: A retrospective review of Duke University and Durham VA charts was performed for men with adenocarcinomas of the prostate and RS colon from 1988-2017. Synchronous presentation was defined as symptoms, diagnosis (dx), or treatment (tx) of PC/RSC within 12 months. The primary endpoint was overall survival (OS), calculated from latest dx date. Univariate and multivariate (MVA) Cox regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Liu et al, 2011; Sturludóttir et al, 2015). Compared with Sturludóttir et al, who analyzed the association between PC and rectal cancer over a period of 16 years, Jacobs et al reported a twofold higher incidence for synchronous PC and rectosigmoid cancer over a period of 20 years (Jacobs et al, 2020; Sturludóttir et al, 2015). Another study from Czech Republic showed that 2.3% of patients diagnosed with CRC between 2003 and 2013 and followed until 2018 developed PC (Halamkova et al, 2021), in line with a Swedish study that has shown that 1.9% of those over 72,000 patients have associated colon cancer and PC (Van Hemelrijck et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Liu et al, 2011; Sturludóttir et al, 2015). Compared with Sturludóttir et al, who analyzed the association between PC and rectal cancer over a period of 16 years, Jacobs et al reported a twofold higher incidence for synchronous PC and rectosigmoid cancer over a period of 20 years (Jacobs et al, 2020; Sturludóttir et al, 2015). Another study from Czech Republic showed that 2.3% of patients diagnosed with CRC between 2003 and 2013 and followed until 2018 developed PC (Halamkova et al, 2021), in line with a Swedish study that has shown that 1.9% of those over 72,000 patients have associated colon cancer and PC (Van Hemelrijck et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…The incidence of D/MPMTs with prostate and colorectal origin varies considerably depending on the inclusion criteria, the size and characteristics of the cohort, the involved anatomical region of the large bowel, and the length of the follow-up (Table 3) (Jacobs et al, 2020; Kavanagh et al, 2012; L. Liu et al, 2011; Sturludóttir et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations